The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jen.12211
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural response of the woodwasp Sirex noctilio to volatile emissions of its fungal symbiont

Abstract: The wood-boring wasp, Sirex noctilio, is a global invasive pest that infects and kills pine trees by inoculating spores of a symbiotic fungus (Amylostereum areolatum) at oviposition. Wasp larvae depend on fungal growth to feed, while the fungus relies on female wasps to initially condition the pine tree by inoculating a phytotoxic venom and for dispersal. Wasp larvae use the fungus as an external gut for the digestion of lignocellulosic compounds resulting in a strong correlation between fungal growth inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…Variability in pine colonisation could be because of the host volatile profile. Sirex noctilio exhibits positive chemotaxis to pine monoterpenes (Fernández Ajó et al ., ) and an α : β pinene blend (70 : 30) is currently used for trapping. In the field, Böröczky et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability in pine colonisation could be because of the host volatile profile. Sirex noctilio exhibits positive chemotaxis to pine monoterpenes (Fernández Ajó et al ., ) and an α : β pinene blend (70 : 30) is currently used for trapping. In the field, Böröczky et al .…”
Section: Discussionmentioning
confidence: 99%
“…Variability in pine colonisation could be because of the host volatile profile. Sirex noctilio exhibits positive chemotaxis to pine monoterpenes (Fernández Ajó et al, 2015) and an : pinene blend (70 : 30) is currently used for trapping. In the field, Böröczky et al (2012) found that P. sylvestris trap trees of a high -3-carene chemotype captured more S. noctilio than low -3-carene chemotype P. sylvestris or P. strobus; however, this pattern did not translate to more S. noctilio emergents in attacked hosts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proportion of drill clusters that were pre‐conditioning (one drill/cluster) versus presumably egg‐laying (≥ 2 drills/cluster) did not differ across treatments. Less drilling by S. noctilio into bolts inoculated with A. areolatum could have been an active choice because we know that S. noctilio females can detect A. areolatum volatiles (Fernández Ajó et al ., ; Sarvary et al ., ). Drilling by S. noctilio in bolts inoculated with Aa BD, which is assumed to have been introduced to North America with S. noctilio , was intermediate.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, the most common methods used to weaken host trees are ring cutting and herbicide injection; however, these methods result in the death of the host tree. Fernández Ajó and coworkers showed that volatiles from symbiont are capable of attracting adult woodwasps, and the attractant ability of symbiont volatiles is better than that of host volatiles . However, volatile organic compounds (VOCs) of symbiotic fungus were not assayed in his study.…”
Section: Introductionmentioning
confidence: 98%